Manajemen Anestesi Pada Pasien Rencana Open Reduction and Internal Fixtation (ORIF) + Post Craniotomy - Andini Waltrin (EduInovasi: Journal of Basic Educational Studies, 2024)
Surgery is generally the treatment method of choice for these fractures because of the difficulty in maintaining cast reduction or functional bracing. One of the operative treatments is open reduction and internal fixation (ORIF).  ORIF is a surgical procedure performed with the aim of restoring bone alignment and providing stability to broken bone fragments after a fracture.